(untitled) (Biological Sciences - PJSIR, 2004)
Monochloroderivatives of aromatic amines are the degrada- tion products of commonly used herbicides. The oxidation potential of monochloroanilines at a number of solid elec- trodes has been found to be dependent on the number of substituents in the ring system (Suatoni et al 1961).